Integration of Communication Strategy and Learning Methods in the Formation of Islamic Students' Morals A Case Study at the Khoiru Ummah Islamic Boarding School in Central Maluku - Umi Aminatuz Zuhriyah; Rajab Rajab; Moh. Rahanyamtel (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2026)
This study aims to analyze the integration of communication strategies and learning methods in the formation of noble character in students at the Khoiru Ummah Islamic Boarding School in Central Maluku. The study used a qualitative approach with a case study design. Data were obtained through participatory observation, semi-structured interviews, and documentation of 15 informants consisting of Islamic boarding school leaders, educational administrators, ustaz, musyrif, and students. Data analysis was carried out using the Miles, Huberman, and Saldaña model through data condensation, data presentation, and drawing conclusions, while data validity was tested by triangulation of sources, techniques, and time. The results showed that the formation of noble character was carried out through the integration of redundancy, informative, educative, coercive, and selective communication strategies with learning methods of lectures, questions and answers, discussions, and sorogan. This integration resulted in the process of internalizing Islamic values ​​through habituation, role models, strengthening discipline, interpersonal interaction, and continuous reflection and evaluation. The implementation of communication strategies is supported by communicator competence, a culture of exemplary behavior, adequate facilities and infrastructure, and organizational openness. While language and cultural differences, the physical and psychological conditions of students, communication prejudices, and time constraints are inhibiting factors. This research produces a conceptual model of the integration of communication strategies and learning methods that contributes to the development of Islamic educational communication theory and serves as a practical reference in strengthening Islamic boarding school-based character education.